Value Creation in Public-Private Partnerships. A case study from the mobile Health sector in Tanzania - Foschi, Annachiara (2015)
Purpose- The purpose of this research is to investigate the evidence of value creation within a Public-Private Partnership (Wazazi Nipendeni) in Tanzania, in the mobile Health (mHealth) sector. Using the Collaborative Value Creation (CVC) framework by Austin and Seitanidi (2012a; 2012b), the research aims at understanding the sources of value of the case study and the types of values produced in the PPP. It also wants to show the processes of value creation, where value gets created and who benefits from it, to have a comprehensive idea of the value creation within the case study.